The Teachers’ Online Readiness: an evaluation of Online Learning during Covid-19 Pandemic in Indonesia - Arifianto, Chandra Fitra; Mutawali; Subekti, Heny (International Journal of Social Learning (IJSL), 2021)
Online learning is the right choice to do during the Covid-19 pandemic. So that the challenges that teachers in implementing learning must face are in themselves. Therefore, this study assesses the influence of attitudes, interests, and motivation on teachers' online readiness in learning from home due to the Covid-19 pandemic. This research is quantitative by using a questionnaire for data collection. The sample was determined using an accidental sampling method, namely elementary school teachers and equivalent to senior high school teachers and equivalent from all regions of Indonesia, totaling 281 respondents. While the analysis technique used is multiple linear regression. The results of this study indicate that attitude has a significant influence on online readiness, with the most dominant indicator being behavior, interest also has a significant influence on online readiness, with the most dominant indicator being personal, and motivation has a minor influence on online readiness with the most indicator dominant being external. While simultaneously, attitudes, interests, and motivation positively affect online readiness with a significance level of less than 0.005. Due to the limited variables chosen, it is recommended to enrich it using other variables in further research.